IBADURRAHMAN VALUE EDUCATION MODEL IN SCHOOL - Uus Ruswandi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
This study is based on two different phenomena among few of students. On one side, some students have excellent achievement that is gained through optimal training process from all parties. On the other hand, some students do several misbehaviour actions such as fighting, raping, murdering, robbery, pornography, drinking alcohol, selling drugs, and mysticism that can ruin aqidah. This study aims to explain the development of value education model based Ibad al-Rahman character especially its vision, mission, program, situation, process, support from society, parents, and students and evaluation in order to train to be akhlaqul karimah personality. This study reveals some findings that the development of value education based on ‘Ibad al-Rahman character can assist to achieve school‟s vision, mission, objective, situation and condition and make it easy to realize education obejctive of ‘Ibad al-Rahman. In short, education process through habituation and exemplary is the most exact method and sufficient support from internal and external sides to bear ‘Ibad al-Rahman character, and evaluation is done in the development of value education based on ‘Ibad al-Rahman character in school.